Reciprocal Multifaceted Interaction Between HDL (High-Density Lipoprotein) and Myocardial Infarction. Issue 8 (August 2019) - Sposito, Andrei C.; de Lima-Junior, José Carlos; Moura, Filipe A.; Barreto, Joaquim; Bonilha, Isabella; Santana, Michele; Virginio, Vitor W.; Sun, Lufan; Carvalho, Luiz Sergio F.; Soares, Alexandre A.S.; Nadruz, Wilson; Feinstein, Steve B.; et al.
Abstract : Despite decades of therapeutic advances, myocardial infarction remains a leading cause of death worldwide. Recent studies have identified HDLs (high-density lipoproteins) as a potential candidate for mitigating coronary ischemia/reperfusion injury via a broad spectrum of signaling pathways. HDL ligands, such as S1P (sphingosine-1-phosphate), Apo (apolipoprotein) A-I, clusterin, and miRNA, may influence the opening of the mitochondrial channel, insulin sensitivity, and production of vascular autacoids, such as NO, prostacyclin, and endothelin-1. In parallel, antioxidant activity and sequestration of oxidized molecules provided by HDL can attenuate the oxidative stress that triggers ischemia/reperfusion. Nevertheless, during myocardial infarction, oxidation and the capture of oxidized and proinflammatory molecules generate large phenotypic and functional changes in HDL, potentially limiting its beneficial properties. In this review, new findings from cellular and animal models, as well as from clinical studies, will be discussed to describe the cardioprotective benefits of HDL on myocardial infarction. Furthermore, mechanisms by which HDL modulates cardiac function and potential strategies to mitigate postmyocardial infarction risk damage by HDL will be detailed throughout the review.